Metode Economic Value Added Untuk Menganalisis Kinerja Keuangan Bank Umum Pemerintah - Miftachulfia, Aulia Wahyu; Sholeh, Rachmad (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2022)
An assessment of a bank's financial performance can interpret the actual condition of the bank. The concept of Economic Value Added (EVA) is an appropriate and effective alternative to be used in measuring bank performance where the focus of performance assessment is on the creation of bank value. The purpose of this study is to determine the financial performance of Government Commercial Banks using the Economic Value Added (EVA) method. The technical analysis used in this study is a descriptive quantitative analysis, where the data used is secondary data obtained from the official website of the Indonesia Stock Exchange—methods of collecting documentation data and literature research. The sampling technique in this study was taken by purposive sampling. The research sample of Government Commercial Banks consists of Bank Mandiri, BNI, BRI, and BTN. Analysis of research results based on the calculation steps of Economic Value Added (EVA). The results of this study show that (1) NOPAT values fluctuate and tend to be negative. (2) The value of Invested Capital fluctuates due to the unstable amount of bank equity, (3) The value of WACC has a negative tendency in each year of the study, (4) Capital Charges also fluctuate even though there are some positive values, (5) The Economic Value Added (EVA) results have only one positive result, namely Bank BTN (Persero) Tbk. This shows that Bank BTN can create added value maximize income and minimize bank expenses.